The Tehnički leksikon and Croatian Technological Terminology - Zvonimir Jakobović (Studia Lexicographica, 2019)
This paper offers an overview of the creation and development of Croatian technological and natural science terminology. The context in which terminology – language and its component concepts, terms, and definitions – developed has been determined, and then been applied to professional terminology. The development of Croatian professional terminology, from its spontaneous appearance in general language, its first recording in early Croatian dictionaries, through the first professional books from the time when the Croatian language was introduced into schools, to its application at the time of economic development and the development of higher education, has been examined. The principles of professional terminology formation, the principles of translating from other languages, and the rules of applying such terminology have been set down. The paper concludes with a description of how these research results were applied to the selection and formation of terminology in the Tehnički leksikon (Lexicon of Technology), linked to the terminology in world languages.